Mechanosensitive miRNAs in Cartilage and Subchondral Bone Remodeling: Emerging Targets for Osteoarthritis Therapy - Shang X (Journal of Inflammation Research)
Xiaobin Shang Department of Orthopedics, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of ChinaCorrespondence: Xiaobin Shang, Email shangxiaobin0929@163.comAbstract: Osteoarthritis (OA) is a chronic degenerative joint disorder characterized by cartilage degradation and bone remodeling. Mechanical stimuli play fundamental roles in maintaining joint homeostasis by regulating cellular metabolism and the composition and stiffness of the extracellular matrix (ECM). Consequently, targeting mechanics-associated factors represent a promising therapeutic direction for OA. MicroRNAs (miRNAs), a class of short non-coding RNAs, negatively regulate target mRNAs at the posttranscriptional level and modulate gene expression in recipient cells without altering gene sequences. Growing interest surrounds the impact of mechanical forces on cellular responses and associated epigenetic gene expression. Therefore, investigating miRNA expression under mechanical loading conditions is crucial for elucidating the role of mechanosensitive miRNAs in articular cartilage and bone metabolism. This highlights specific miRNAs as potential therapeutic targets to disrupt the pathological feedback loops in OA. In this review, we examine the current applications of mechanosensitive miRNAs and delivery systems for OA therapy. We further analyze potential factors influencing their application. Significantly, extracellular vesicles (EVs) may facilitate the transport of mechanosensitive miRNAs across the bone–cartilage interface under mechanical stress. This mechanism provides a novel perspective for fully understanding the bidirectional communication between chondrocytes and osteocytes in response to physiological loading, and how its dysregulation contributes to OA pathology. Advancing research on EVs and their miRNA cargo is essential for the effective application of mechanosensitive miRNA-based regulation in intercellular and tissue interactions during OA treatment.Keywords: osteoarthritis, mechanosensitive, microRNAs, extracellular vesicles